Detection of Metallo-β-Lactamases (MBLs) Producing Pseudomonas aeruginosa Isolates in Tehran Hospitals, Iran - Mohsen Tabasi; Reza Azizian; Mohammad Reza Eskandarion; Mehri Habibi; Mohammad Reza Asadi Karam (Pasteur Institute of Iran, 2017)
Introduction: The strains of Pseudomonas aeruginosa are known as an opportunistic pathogen that can cause infections in humans and animals. Metallo-β-lactamases (MBLs) are the most significant factors of resistance to carbapenem antibiotics in these bacteria. This study was designed to identify the MBLs producing P. aeruginosa isolates in three hospitals of Tehran, Iran. Methods: Totally, we obtained 665 samples from patients hospitalized in three hospitals in Tehran, Iran. Antibiotic-susceptibility test of the P. aeruginosa isolates was done based on Kirby-Bauer disk diffusion test. The Minimum Inhibitory Concentration (MIC) of the isolates was performed using agar dilution method, and IPM-EDTA test identified MBL producing isolates. Results: Among the examined isolates, 473 (71.1%) were P. aeruginosa. Among these, 306 (64.7%) were resistant to imipenem, and 289 (94.5%) were MBL producers. Furthermore, the resistance rate of the isolates to other antibiotics was amikacin (26%), tobramycin (24.95%), ceftazidime (23.05%), gentamicin (22.83%), carbenicillin (21.14%), and ceftizoxime (18.19%). The MICs of imipenem and ceftazidime for the majority of the isolates were 4 µg/ml and ˃128 µg/ml, respectively. Conclusion: This study confirmed previous reports on the increased rate of MBL-mediated resistance in P. aeruginosa isolates worldwide. Therefore, detection of resistance patterns for these isolates, particularly MBLs, is necessary for prevention and control of Pseudomonas associated infections.